NLP Mirroring Strategy To Improve Students' Empathy Character In Virtual Interaction - Novita Sari Hutapea; Rita Hartati; Nurul Indah Ramadina; Rizqi Fadhilah Hidayah; Marta Friska Tindaon; May Devi Triana; Sepania Handayani Sihite (Journal on Education, 2024)
In the digital era, fostering empathy among students in virtual interaction settings has emerged as an important goal of educators and practitioners. This study investigates the effectiveness of Neuro-Linguistic Programming (NLP) mirroring strategies in improving students' empathetic character in virtual interactions, using a mixed-methods research design. Quantitative data were collected through pre- and post-intervention surveys administered via Google Forms to measure the students' levels of empathy. Qualitative data were collected through observations, interviews, and Forum Group Discussions (FGDs). Triangulating quantitative survey data with qualitative findings provided a comprehensive analysis of the impact of NLP mirroring strategies on student empathy in the context of virtual interactions. Participants in this research were 30 students in the 6th semester of the Medan State University (UNIMED) English Literature Study Program. The findings of this study have implications for educators, policymakers, and practitioners who wish to improve empathy and interpersonal skills in digitally funded educational settings. By illuminating the potential of NLP mirroring as a pedagogical tool, this study informs the development of evidence-based strategies to promote empathy and social-emotional learning in virtual learning environments.